CHARACTERIZATION OF MOSQUITO ANTIMICROBIAL PEPTIDES (AMPS) USING COMPUTATIONAL TOOLS AND ONLINE SERVERS - K. VANLALHRUAIA (International Journal of Pharma and Bio Sciences, 2014)
In this paper, nineteen different Anti-microbial peptides (cecropin, degensin and gambicin) of mosquito retrieved from National Centre for Biotechnology Information (NCBI) database were analysed and characterized using In silico tools. Primary structure analysis shows that most of the AMPs are hydrophobic in nature due to the high content of non-polar residues. The presence of Cysteines residues was found only on defensin AMPs of Anopheles gambiae, Culex quinquefasciatus, Aedes aegypti, Aedes albopictus, Culex pipiens and Anopheles stephensi infer that these proteins may form disulphide (SS) bonds, which are regarded as a positive factor for stability. The aliphatic index computed by Ex-Pasy’s ProtParam infers that AMPs may be stable for a wide range of temperature. Secondary structure analysis shows that most of the AMPs mixed secondary structure. The presence of disulphide (SS) bonds in the Q7PY14.4, ABB00933, EDS293341, AAC36346, AAO38519 and ABM92299 were predicted by CYS_REC tool and also identified from the three-dimensional structure using Rasmol tool. The disulphide bonds identified from the three-dimensional structure using the Rasmol tool might be correct as the evaluation parameters are within the acceptable limits for the modeled 3D structures.